(untitled) (Kerala Journal of Psychiatry, 2022)
Background: In Kerala, according to National Family Health Survey 4, 37.5% of males and 1.6% of females use alcohol. Even though the physical and mental health morbidity of alcohol dependence is well-known, studies are less. The study assessed the severity of alcohol dependence and its different socio-demographic and clinical correlates. Materials and Methods: A hospital-based cross-sectional study was conducted among alcohol dependence syndrome patients. Total sample size 100 was achieved by consecutive sampling. Data was collected using a semi-structured proforma, which included severity of alcohol use using severity of alcohol dependence questionnaire (SADQ). Chi-square test and logistic regression analysis were done to find the relationship between variables. Results: All the participants were males. The majority were between 30-60 years, from a rural background (64%), belonged to low socioeconomic (85%) nuclear families (65%). The majority of the participants had started using alcohol before 20 years of age (85%), were using alcohol for more than ten years (97%), had comorbid nicotine use (80%), at least one previous admission (91%) and a positive family history of alcohol use (72%). All the participants in the study had moderate to severe ADS. On comparing different variables with the severity of ADS, age of onset, the number of previous admissions and comorbid nicotine use were significant. Logistic regression analysis found the age of onset (p-value 0.019) and nicotine use (p-value 0.002) as the predictors of severity of ADS. Conclusion: Study points to the need for early intervention programs targeting the high-risk population and the need for addressing nicotine use among persons with ADS.